Odpowiedzi

Najlepsza Odpowiedź!
2009-12-21T19:43:57+01:00
2(x-2)+4(y-3)=-2
x-y=-2

2x - 4 + 4y - 12 = -2
x - y = -2

2x + 4y = -2 +4 +12
x - y = -2

2x + 4y = 14
x - y = -2 |*4

2x + 4y = 14
4x -4y = -8

6x = 6|:6
x = 1

x - y = -2
1 - y = -2
-y = -2-1
y = 3


2x+3y=15
3(x-2)-(4-y)=2

2x + 3y = 15
3x - 6 - 4 + y = 2

2x + 3y = 15
3x + y = 2 + 6 + 4

2x + 3y = 15
3x + y = 12 |*(-3)

2x + 3y = 15
-9x - 3y = -36

-7x = -21 |: (-7)
x = 3

2x + 3y = 15
2*3 + 3y = 15
3y = 15 - 6
3y = 9 |:3
y = 3
2009-12-21T19:52:02+01:00
2(x-2) + 4(y-3) = -2
x-y=-2

2x -4 +4y -12 = -2
x-y = -2

2x +4y = -2 +16
x-y = -2

2x +4y = 14
x-y=-2 |*(-2)

2x+4y = 14
-2x -2y = -4

2y = 10 | :2
y= 5

y=5
x-5=-2

y=5
x= -2+5

y=5
x= 3


2x+3y=15
3(x-2)-(4-y)=2

2x+3y=15
3x -6 -(4+y)=2

2x+3y=15
3x-6 -4 +y=2

2x+3y=15
3x -10 +y =2

2x+3y=15
3x +y= 2 +10

2x+3y=15
3x+y= 12 |* (-3)

2x+3y=15
-9x -3y=-36

-7x= -21 |:(-7)
x= 3

x=3
2x+3y=15

x=3
2*3+3y=15

x=3
6+3y=15

x=3
3y=15-6

x=3
3y=9|:3
x=3
y=3
:)) koniec